Hubungan Status Gizi, Asupan Lemak dan Zat Besi terhadap Kejadian Dismenorea pada Mahasiswi Gizi Universitas Negeri Surabaya - R. Aj. Nabila Nur Syahlah Zhafirah; Choirul Anna Nur Afifah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Dysmenorrhea is one of the most common menstrual disorders, but it often receives little attention. The purpose of this study was to determine the relationship between nutritional status, fat intake, and iron intake with the incidence of dysmenorrhea in female Nutrition students at Surabaya State University. The method in this study was quantitative with a cross-sectional study design. The sample consisted of 92 female Nutrition students at Surabaya State University using a purposive sampling technique. The instruments used were the NRS questionnaire to measure the level of dysmenorrhea pain and the SQ-FFQ form to measure fat and iron intake. Data analysis used the Spearman Rank correlation test which showed that there was a significant relationship between excess nutritional status of 33.7% with the incidence of dysmenorrhea (p = 0.000, r = 0.832), there was a significant relationship between excess fat intake of 58.7% with the incidence of dysmenorrhea (p = 0.000, r = 0.793), and there was a significant relationship between insufficient iron intake of 94.6% with the incidence of dysmenorrhea (p = 0.000, r = 0.610).